Leadership perspective between leaders and subordinates in a marketing communication agent company - Ida Bagus Gede Adi Permana, Andre Astri Desis Prasetyo, (Opción, 2020)
The phenomenon that occurs nowadays is the distance between leaders and subordinates due to their different statuses. This gap can be anticipated by using the perspective of the Leadership Member Exchange (LMX) in leaders and subordinates. This study aimed to determine social exchanges between leaders and subordinates with LMX perspectives in a marketing communication agent company using phenomenological approach with LMX perspective. It was found four findings on how to build communication, hold outings or vacations, and benefit from outside activities of work. There was high quality LMX perspective between leaders and subordinates at a marketing communication agent company.